Generation of electrical energy with a stirling engine using a gas fuel - Lira Cacho, Guillermo (2007)
A low-power, relatively low-cost, beta-type Sirling engine is proposed for the generation of electrical or mechanical energy using a gaseous fuel. Aspects related to the design, construction and experimental tests of this prototype are shown, including the thermodynamic analysis of the motor and the kinematic calculation of the rhombic movement transformation mechanism. To facilitate and optimize the motor design, a mathematical model based on Schmidt's general theory of these motors was developed. The results of the tests carried out at the Institute of Internal Combustion Engines of the UNI with a 60 W prototype using LPG are included.